Determining the effect of motivations and behavior to the social entrepreneurial intentions of the Philippine youth - Galang, Carlos Miguel G. (Animo Repository, 2021)
Social enterprises are businesses that have a specific social objective that serve its primary purpose. These enterprises look to maximize profits while ensuring that these benefit the society especially to those who need the most help. Social enterprises are driven by the social entrepreneur’s mission and vision to create positive change in their surroundings. This study seeks to determine the effect of motivations and behavior to the social entrepreneurial intentions of the Philippine youth. The respondents of the study include 384 respondents under the bracket of the Philippine Youth (ages 18-35) located in Metro Manila. In addition, 5 members from the Lasallian Social Enterprise for Economic Development (LSEED) were interviewed. The Lasallian Social Enterprise for Economic Development (LSEED) is an organization established in De La Salle University - Manila that is centered on helping students address society’s problems such as poverty, climate change, overpopulation, health care availability, gender inequality, civil rights and racial discrimination, etc. through social entrepreneurship. This study is the first to attempt to link these five variables in coherence with one another. The study’s independent variables, which are the antecedents of social entrepreneurial intentions include social support, moral obligation, prior experience, self efficacy and empathy. The moderating variables of the study include intrinsic motivation, prosocial behavior and antecedents to motivation (perceived feasibility and perceived desirability). Lastly, the study’s dependent variable are social entrepreneurial intentions. In the findings of the study using simple linear regression analysis, prior experience is the most significant variable towards social entrepreneurial intentions for the Philippine youth as shown in the study, this is followed by empathy, self efficacy, social support then moral obligation. Through multiple regression findings show there are no moderating effects between the antecedents of social entrepreneurial intentions and antecedents of motivation, prosocial behavior and intrinsic motivation towards social entrepreneurial intentions. Although, this happens when the independent variables and moderating variables are examined as one whole theory to another, as seen in the framework. In addition, with the given set of empirical findings, the researchers further tested each antecedent independently to each moderating variables and there were significant moderating effects between Perceived Desirability and Empathy, Perceived Desirability and Prior Experience, Perceived Feasibility and Moral Obligation, Intrinsic Motivation and Moral Obligation.